Use of platelet large cell ratio as a new biomarker in the diagnosis of acute appendicitis - Celik, Muhammet; Tekin, Erdal; Bayraktar, Mustafa (Journal of Surgery and Medicine, 2020)
Aim: Acute appendicitis (AA) is one of the common causes of acute abdomen. Despite classical signs and symptoms, it may not always be easily and quickly diagnosed. Although many laboratory and imaging methods and risk scoring systems are available, studies are currently underway to find new biomarkers. In this study, we aimed to investigate whether Platelet-Large Cell Ratio (P-LCR), one of the platelet parameters, can be used as a new biomarker. Methods: This retrospective cross-sectional study was performed by scanning the hospital records of AA patients, as determined with histopathological examination, who were diagnosed between 01 January-November 2019. The patients were divided into three as normal appendectomy (Group 1), non-complicated appendicitis (Group 2) and complicated appendicitis (Group 3) groups, which were compared in terms of P-LCR and other platelet parameters. Results: A total of 425 patients were included in the study. The number of female patients in Groups 1, 2 and 3 were 12 (36.4%), 42 (45.7%), and 121 (40.3%), respectively. The mean age of the patients was 27.2 (16.1) years. Among all, complicated and uncomplicated appendectomy groups had significantly higher WBC and lower PDW and P-LCR values compared to the normal appendectomy group (P=0.007, P=0.027 and P=0.036, respectively). The cut-off values of WBC and P-LCR were 11.47 (71.9% sensitivity, 51.5% specificity) and 19.85 (75.8% sensitivity, 32.4% specificity), respectively. The WBC and P-LCR values had strong distinguishing features compared to other parameters (AUC=0.630, P=0.013 and AUC=0.604, P=0.047, respectively). Conclusion: This is the first study investigating the P-LCR value in the diagnosis of AA. We found that WBC, PDW and P-LCR values, which are whole blood count parameters, can be used in the diagnosis of AA.